OUTCOME OF PYELOPLASTY IN CHILDREN - Siddique, Muhammad; Pansota, Mudassar Saeed; Saleem, Muhammad Shahzad; Rehman, Attique -ur- (Journal of Ayub Medical College Abbottabad, 2014)
Background: Hydronephrosis in children is a common congenital urologic problem with pelviureteric junction obstruction being its most common cause. This study was conducted to evaluate the outcome of pyeloplasty for congenital pelviureteric junction obstruction in children. Methods: This study was conducted in department of Paediatric Surgery, Quaid-e-Azam Medical College/Bahawal Victoria Hospital, Bahawalpur from July 2008 to December 2010. A total of 50 patients diagnosed on ultrasonography and intravenous urogram as having PUJ obstruction were included. Patients with history of previous repair were excluded. Both Dismembered (Anderson Hynes) and Non-dismembered (Flap procedures) pyeloplasties were performed depending upon the size of pelvis and degree of dilatation. Initial follow-up was after 1 week, then after 15 days and then monthly for 3 months. Minimum follow-up period was 6 months and maximum 15 months. At three month, excretory urography was obtained to assess the function of that particular renal unit. Results: Lumbar pain and flank mass were the commonest presenting complaints. Thirty-six (72%) patients were male. Left sided obstruction was in 32 (64%) cases, right-sided in 15 (30%), and 3 (6%) cases were bilateral. Common post-operative complications were urinoma formation and re-stenosis in two cases each. There was also no gross difference of outcome in pyeloplasty whether done with or without double-J (DJ) stents. Moreover, dismembered pyeloplasty resulted in better outcome. Conclusions: Open pyeloplasty is the Gold Standard treatment option for congenital pelviureteric junction obstruction. The use of DJ Stents is not necessary in every repair. Keywords: Pelviureteric junction Obstruction, Ultrasonography, intravenous urogram, dismembered pyeloplasty, non-dismembered, pyeloplasty, DJ Stent